Analisis Gamification Shopee.com Sebagai Media Pemasaran Terhadap EWOM, Positive Emotion, & Repurchase Intention (Pada Aplikasi Shopee.com) - Chrisnathaniel, Hendy; Hartini, Sri; Rahayu, Sari Puji (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2021)
This study aims to explore the influence of Shopee.com gamification as a marketing media for EWOM, positive emotion, and repurchase intention. Researchers emphasize on Shopee as one of the e-commerce that is first ranked with the number of monthly web visitors, and first ranked on the Appstore and Playstore in Indonesia. This study uses a questionnaire distributed online to 170 respondents, with criteria as the "Y" generation, and has used Shopee and has the experience to use the loyalty games program of the Shopee.com application. The results of this study were further processed and analyzed with the Structural Equation Modeling (SEM) statistical technique with the smartPLS 3.0 program. The results showed that Shopee.com gamification had a positive effect on positive emotion, repurchase intentions, and electronic word of mouth (EWOM). Then positive emotion has a positive effect on repurchase intentions and electronic word of mouth (EWOM).